2021
DOI: 10.1155/2021/5546338
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multitask Joint Sparse Representation Algorithm in Chinese Painting Image Classification

Abstract: This paper presents an in-depth study and analysis of Chinese painting image classification by a multitask joint sparse representation algorithm for texture feature extraction of Chinese painting images and proposes a method to extract texture features directly for the original images. It simplifies the process of image grayscale conversion and preserves the information contained in the original Chinese painting images to the greatest extent. The algorithm uses the ideas of multicolor domain analysis and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…e research on low-level feature extraction, data compression, automatic semantic annotation, retrieval, and automatic classification of digital Chinese painting image is more and more extensive [6]. Yang et al [7] found that the research on automatic classification and annotation of digital images of Chinese painting involves the integration of computer vision, machine learning, image retrieval, cognitive psychology, and painting art. In general, because there is no direct relationship between the low-level visual features and high-level semantic concepts of Chinese painting images, the automatic semantic classification and annotation of Chinese painting images is a very challenging research topic [7].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…e research on low-level feature extraction, data compression, automatic semantic annotation, retrieval, and automatic classification of digital Chinese painting image is more and more extensive [6]. Yang et al [7] found that the research on automatic classification and annotation of digital images of Chinese painting involves the integration of computer vision, machine learning, image retrieval, cognitive psychology, and painting art. In general, because there is no direct relationship between the low-level visual features and high-level semantic concepts of Chinese painting images, the automatic semantic classification and annotation of Chinese painting images is a very challenging research topic [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yang et al [7] found that the research on automatic classification and annotation of digital images of Chinese painting involves the integration of computer vision, machine learning, image retrieval, cognitive psychology, and painting art. In general, because there is no direct relationship between the low-level visual features and high-level semantic concepts of Chinese painting images, the automatic semantic classification and annotation of Chinese painting images is a very challenging research topic [7]. Li et al [8] have studied content-based image retrieval (CBIR) and image classification technology for more than ten years.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These harmful substances will accelerate the damage and destruction of Chinese paintings. Sulfur substances and harmful factors in the air will accelerate the damage to Chinese paintings [ 7 , 8 ]. For Han painting, it mainly shows the contemporary economic and political development trend through the patterns, colors, and painting forms of Han painting.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, they can not only express their feelings in the works, but also make the images have emotion and vitality. Emotion is the driving force of Chinese painting creation (Bi et al, 2019;Yang et al, 2021). Traditional algorithms to recognize human affects in Chinese paintings often combine art theory and computer vision, practicing artificially designed features and statistical ML (Machine Learning) approaches to recognize the emotional responses evoked by Chinese paintings.…”
Section: Demand For Chinese Painting Emotion Recognitionmentioning
confidence: 99%